2002
DOI: 10.1046/j.1460-9568.2002.02185.x
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal reorganization of primary afferent input and dorsal horn cell receptive fields in the rat spinal cord is an activity‐dependent process

Abstract: The dorsal horn of the spinal cord in the newborn rat is characterized by large cutaneous mechanoreceptive fields, a predominance of A-fibre synaptic inputs and diffuse primary afferent A-fibre projections, all of which are gradually reduced and refined over the first postnatal weeks. This may be partly responsible for the reduction in cutaneous flexion reflex sensitivity of rats over the postnatal period. Here we show that chronic, local exposure of the dorsal horn of the lumbar spinal cord to the NMDA antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 59 publications
2
124
0
Order By: Relevance
“…LPS is a bacterial endotoxin that activates Toll-like receptor 4 and subsequently MAPK and NF-B signaling pathways in microglia involved in the release of proinflammatory cytokines TNF␣ and IL-6 that also efficiently downregulate IL-10 (Harry, 2013). LPS-activated microglia release TNF at lower concentrations than the single TNF injection administered here (Welser-Alves and Milner, 2013;Berta et al, 2014); these lower levels of TNF sensitized young SNI mice, while leaving sham animals of the same age unaffected. However, despite being able to respond to stressors such as TNF or LPS-activated microglia, infant mice do not normally produce TNF and BDNF following infant nerve injury, due to an anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…LPS is a bacterial endotoxin that activates Toll-like receptor 4 and subsequently MAPK and NF-B signaling pathways in microglia involved in the release of proinflammatory cytokines TNF␣ and IL-6 that also efficiently downregulate IL-10 (Harry, 2013). LPS-activated microglia release TNF at lower concentrations than the single TNF injection administered here (Welser-Alves and Milner, 2013;Berta et al, 2014); these lower levels of TNF sensitized young SNI mice, while leaving sham animals of the same age unaffected. However, despite being able to respond to stressors such as TNF or LPS-activated microglia, infant mice do not normally produce TNF and BDNF following infant nerve injury, due to an anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 71%
“…The predominant anti-inflammatory response during the postnatal period may prevent excessive responses to microbes following the transition from the sterile environment in utero (Maynard et al, 2012) and facilitate microglial "synaptic stripping," removing damaged cells and dysfunctional synapses during development (Kettenmann et al, 2013). In other words, the antiinflammatory response to nerve damage in infants may be the indirect consequence of the requirements for normal postnatal development in the dorsal horn (Beggs et al, 2002;Bremner and Fitzgerald, 2008;Koch et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that low-threshold A␤-fiber input to the SDH is more pronounced during the neonatal period (Beggs et al 2002;Daniele and MacDermott 2009;Jennings and Fitzgerald 1996) and becomes subject to tight inhibitory control at later ages (Torsney and MacDermott 2006). However, since primary afferents may target subtypes of SDH neurons in a highly selective manner Perl 2003, 2005;Zheng et al 2010), it remains to be determined whether newborn spinal projection neurons do in fact receive enhanced low-threshold sensory input.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies have also confirmed that extensive reorganization of synaptic connections occurs in the SDH during development. The combined effect of this reorganization is to refine peripheral receptive field size, increase mechanical thresholds, and alter the contribution of large-fiber inputs (Beggs et al 2002;Jennings and Fitzgerald 1998;Park et al 1999;Torsney and Fitzgerald 2002).…”
Section: Introductionmentioning
confidence: 99%